Pelestarian Olahraga Tradisional di Kota Kediri melalui FORDESWITA sebagai Upaya Meningkatkan Potensi Perkembangan Ekonomi Berbasis Pariwisata - Puspodari, Puspodari; Himawanto, Wasis; Junaidi, Slamet; Atrup, Atrup; Sukmana, Abdian Asgi; Lusianti, Septyaning; Kurniawan, Rafli Qaulan (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2024)
The city of Kediri has great potential in tourism development. Sumber Jiput has succeeded in winning the 2024 Indonesian Tourism Village Award (ADWI). Perched in the top 300 tourism villages out of a total of 6,601 villages throughout Indonesia. Sumber Jiput in Kediri City is not only an attractive tourist destination, but also a model in developing sustainable tourist areas. Sumber Jiput combines natural beauty and local wisdom while still paying attention to ecological sustainability, making it an increasingly popular tourist destination. Apart from that, which is no less important, one of the main reason is because the city of Kediri is known as a city that uphoulds the values of tolerance. This is proven by the success of maintaining its position in the top 10 most tolerant cities for three consecutive years. This tolerance is a strong foundation for creating an atmosphere conducive to tourism development. This is a very appropriate step to answer current market needs. People can get closer to sports activities and the tourism ecosystem, while enjoying the culinary specialties of the city of Kediri which are increasingly developing. Throught the Fordeswita event, it is hoped introduce the tourism potential of Kediri City. Especially Sumber Jiput to the wider community while improving community welfare throught tourism based economic development.